Immunological efficacy of hepatitis B vaccine - E. V. Eesaulenko; E. N. Prijma; V. V. Skvoroda; V. V. Vetrov; M. M. Remizov; G. F. Trifonova; I. P. Fedunjak (Журнал инфектологии)
Aim: Analyse changes in the intensity of humoral immunity against hepatitis B depending on the duration of the post-vaccination period to assess the effectiveness of vaccination and factors affecting it.Materials and methods. The study was conducted by questionnaire method, during which an epidemiological history was collected from 409 persons aged 18 to 36 years who were not infected with hepatitis B virus. Absence of data on vaccination or presence of HBV markers was an exclusion criterion. Information about hepatitis B vaccination was confirmed by medical documentation, including form No. 156/u-93. All volunteers underwent vaccine audit, including determination of HBV vaccination status, presence of irregularities in the vaccination regimen, dosage, determination of the series of the administered preparation and date of vaccine administration.Epidemiological and statistical methods of research (software product ‘WinPepi’ (version 11.65)) were used in the work. When assessing the statistical significance of differences in the compared epidemiological indicators, the 95% confidence interval was taken into account.Results. Among the subjects aged 18-36 years (21.8 ± 2.7), timely vaccination (within the first 24 hours of life) was performed in 3.4% (n=13) of cases, 7.9% (n=30) were vaccinated in the first year of life and 9.9% (n=38) between one and two years of age. The highest percentage of vaccinated (42.1%) were children aged 7–11 years. The lowest vaccination coverage was determined among adults – 1.8%. Longterm post-vaccination immunity (17 years) was established in the subjects whose age of vaccination coverage was the first three years of life. In those vaccinated with the full scheme, intense immunity is maintained for over 20 years in 100% of cases. After revaccination, a high protective antibody titer was observed in the first five years and amounted to 101-1000 mIU/ml in 55.56% of cases and more than 1000 mIU/ml in 11.11%. A decrease in the protective antibody titer in those who received revaccination was noted after 11-15 years, when the proportion of non-immune individuals was 33.3%.Conclusion. Long-term post-vaccination immunity was formed with vaccination coverage in the first three years of life. In those vaccinated with the full scheme, intense immunity was maintained for over 20 years. If the vaccination scheme is violated, the immunological response weakens and revaccination is required. The need for a booster dose occurs after 11-15 years.